Isolation and characterization of RNA ligase from wheat germ. - Furneaux, H (1983)
A RNA ligase from wheat germ has been extensively purified. In the presence of ATP these enzyme preparations catalyze the covalent linkage of 5'-phosphate and 2',3'-cyclic phosphate termini of RNA chains. Concomitant with the formation of a 3',5'-phosphodiester linkage, the 2',3'-cyclic phosphate is converted to a 2'-phosphate ester, in accord with the findings of Konarska et al. [Konarska, M., Filipowicz, W. & Gross, H. J. (1982) Proc. Natl. Acad. Sci. USA 79, 1474-1478]. The action of the purified enzyme is totally dependent on ATP and on RNA substrates containing a 5'-phosphate terminus at one end and either a 2',3'-cyclic phosphate or a 2'-phosphate terminus at the other end. In the latter case, the reaction is about 30% as active as with the cyclic derivative. In contrast, RNA chains containing 3'-phosphate ends are less than 5% as active as those with the cyclic ends. Purified preparations of RNA ligase have an intrinsic ability to hydrolyze 2',3'-cyclic phosphate termini to 2'-phosphate termini. This reaction is readily detectable in the absence of ATP.